RETROPERITONEAL VS TRANSPERITONEAL LAPAROSCOPIC URETEROLITHOTOMY - Putra, Rosadi; Safriadi, Ferry; Pramod, Sawkar Vijay (Indonesian Urological Association, 2015)
Objective: To compare retroperitoneal versus transperitoneal laparoscopic ureterolithotomy in effectivity, pain scale and early complications. Material & methods: In this prospective comparison study from January 2013 to June 2014, 32 patients with proximal and mid ureteral stones underwent retroperitoneal laparoscopic ureterolithotomy or transperitoneal laparoscopic ureterolithotomy. The randomization occured on consecutive sampling on a 1 : 1 basis. Group 1 and 2 consisted of patients who underwent retroperitoneal laparoscopic ureterolithotomy and transperitoneal laparoscopic ureterolithotomy, respectively. Demographic and clinical variable, operative time, length of stay, ureteral suturing, pain scale according to visual analog scale (VAS) and early complications data were collected and analyzed. Statistical analysis was performed with SPSS® version 17.0 using student T-test and Mann-Whitney U tests with p value < 0.05 considered statistically significant. Results:VAS on day 1 between the 2 groups was statistically significant, and was higher in group 2 (p < 0.05). According to the Clavien-Dindo classification of surgical complication all the patients were in grade 1 classification. The differences in operative time, length of stay, ureteral suturing, visual pain analog score on day 3, and early complications between the 2 groups were not statistically significant.Conclusion: Transperitoneal laparoscopic ureterolithotomy is significantly associated with pain than retroperitoneal laparoscopic ureterolithotomy in first day after surgery. Successful stone removal remains the same in both groups.